Proceso tributario para la devolución del IVA y su incidencia en la liquidez de la exportadora guritbalsaflex cía. Ltda. Del cantón Quevedo período 2022. - Peralta Calero, Jhetsy Marisel (2024)
This research work is oriented to the study of the economic benefits obtained by performing the VAT Refund Processes; being this Technical and Tax, considered, as well as a right to which exporting companies have access, the main objective is to evaluate the incidence of the Tax Process of VAT Refund in the liquidity of the exporter Guritbalsaflex Cía. Ltda. of the canton Quevedo; applying correlational, descriptive and explanatory types of research; as methods the inductive and deductive, the technique is the interview. Through the study it was detected that the processes have been executed correctly during the year 2022, and complying in full with the requirements established by the tax regulatory body in the country (SRI), including two media; physical and digital, making use of the necessary tools provided by the aforementioned body. With the help of these techniques, it was possible to identify the impact that the results of these refund processes have on the company's liquidity, and it was shown how it benefits its cash flow. The population taken for this study was of 8 collaborators of the administrative area of this company who are involved in the subject, this inquiry allowed to acquire sufficient and necessary information to support each of the processes carried out, demonstrating the validity of the techniques used and the logical reasoning of these. The results allowed to measure the level of affection that the immediate VAT refund has on the available cash of Guritbalsaflex Cía. Ltda.